Sex differences in mate selection a study of senior college students of U. P. in the Visayas. - Fabella, Caryl Kate Savillo
Mate selection is one of the most interesting topics of adolescents nowadays. The purpose of this study is to describe sex differences in mate selection among senior college studetns, UPV Iloilo. Specifically, it aims to determine the personal, sociological, and psychological characteristics desired in a mate, and to ascertain the differences in the mate selection criteria of males and females. Stratified random sampling is used in determining the number of respondents, and each of them is given a questionnaire. Simple frequency counts and percentages is used in analyzing the data. The findings showed that males, and females did not generally differ in their mate selection criteria. Both sexes are very willing to marry someone who is responsible, understanding outgoing, resourceful, dependable, independent, earning much more than them, shows respect to their parents or family, regard them with respect, give them equal amount of time and effort, and career-oriented. Moreover, they are not willing to marry someone who is married, has children, belongs to a different religion, and who doesn't love them. However, the diffeences lie in the male respondents being very willing to marry someone who is younger by 5 or more years, while the females prefer a mate who is older to them by 5 or more years., The findings lead to four major conclusions as follows: (1) there are no differences in personal characteristics that males and females look for in potential mates; (2)there is one great diffeence in the sociological characteristics in both males and females pertaining to age, that is men's greater preference for a matewho si younger, and women's greater preference for a mate who is older, (3) there are no differences in psychological characteristics that males and females look for in their potential mates; and (4)males and females are generally similar in their preferences in all of the characteristics with the exception on their preferences regarding with the age of their desired mate. This can be attributed to male's preference for mates with traits that signal their reproductive value, and women on the other hand prefer mates with traits that signal their potential for resource acquisition.